Microparticles in Autoimmunity: Cause or Consequence of Disease? - Rother, Nils; Yanginlar, Cansu; Pieterse, Elmar; Hilbrands, Luuk; van der Vlag, Johan (Frontiers in Immunology, 2022)
Microparticles (MPs) are small (100 nm – 1 um) extracellular vesicles derived from the plasma membrane of dying or activated cells. MPs are important mediators of intercellular communication, transporting proteins, nucleic acids and lipids from the parent cell to other cells. MPs resemble the state of their parent cells and are easily accessible when released into the blood or urine. MPs also play a role in the pathogenesis of different diseases and are considered as potential biomarkers. MP isolation and characterization is technically challenging and results in different studies are contradictory. Therefore, uniform guidelines to isolate and characterize MPs should be developed. Our understanding of MP biology and how MPs play a role in different pathological mechanisms has greatly advanced in recent years. MPs, especially if derived from apoptotic cells, possess strong immunogenic properties due to the presence of modified proteins and nucleic acids. MPs are often found in patients with autoimmune diseases where MPs for example play a role in the break of immunological tolerance and/or induction of inflammatory conditions. In this review, we describe the main techniques to isolate and characterize MPs, define the characteristics of MPs generated during cell death, illustrate different mechanism of intercellular communication via MPs and summarize the role of MPs in pathological mechanisms with a particular focus on autoimmune diseases.